Revision of the Nearctic Parathalassius Mik (Diptera: Dolichopodidae: Parathalassiinae), with a review of the world fauna - Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2017)
The Nearctic species of Parathalassius Mik are revised and the world species are reviewed. Twelve species are recorded from the Nearctic Region including nine new species: P. abela sp. nov., P. aldrichi Melander, P. candidatus Melander, P. dilatus sp. nov., P. infuscatus sp. nov., P. melanderi Cole, P. midas sp. nov., P. sinclairi sp. nov., P. socali sp. nov., P. susanae sp. nov., P. uniformus sp. nov., and P. wheeleri sp. nov. Lectotype designations are made for P. aldrichi Melander and P. melanderi Cole. A key to the 15 world species is provided and the distributions of the Nearctic species are mapped. COI mitochondrial DNA barcode sequences were obtained for 12 species of Parathalassius. A morphological phylogenetic analysis of the included species is presented and known ecological information is summarized.